New molecules and conventional insecticides for the management of tea mosquito bug, Helopeltis antonii in cashew - Smitha, M S; Pushpalatha, P B (Indian Journal of Plant Protection, 2020)
Four new molecules, one insect growth regulator and four conventional insecticides were screened under laboratory and promising insecticides were evaluated under field against tea mosquito bug. Among the new insecticides, thiamethoxam 25 WG performed better and induced a mortality of 93.3 per cent at 48 hours after treatment under laboratory compared to 20, 40 and 26.7 per cent mortality, respectively in spinosad 45 SC, chlorantraniliprole 8 SC and flubendiamide 480 SC. The mortality in acephate, quinalphos and lambda cyhalothrin was 86.7 and 73.3 per cent, respectively. The insect growth regulator, buprofezin did not induce mortality even after 48 hours of treatment. Thiamethoxam performed better and equally effective as standard check, ambda cyhalothrin in reducing the tea mosquito bug incidence in cashew under field. Presently recommended insecticides, quinalphos and lambda cyhalothrin aintained their effectiveness in managing the tea mosquito bug infestation in cashew.